Explanation or Understanding? Movement Studies Between Natural Sciences and Cultural Studies - Eichberg Henning (Sciendo, 2014)
Movement studies are - like health studies - placed between natural sciences and cultural studies as well as between quantitative and qualitative methods. That is why they are challenged by some methodological contradictions. Yet the dual relations between nature and culture, and between quantitative and qualitative methods, may be of superficial character. Deeper beneath, one finds tensions with theoretical implications: between the quest for evidence and the comparative method, between generalization and case study, between explanation and understanding, between the correctness of the answer and the quality of the question, between affirmative and fluent knowledge, between factors and connections, between data and patterns, between the state of research and historical change of knowledge, between objectivity and subjectivity, and between theory and philosophy. There seems to be something akin to cultural struggle in the field of knowledge. Yet the dual contradictions do not comprise two neatly separated "cultures of knowledge" that exclude each other. There are cross-disciplinary connections and overlaps, which help toward an understanding of human life.